Learning cultures of Singaporean freight SMEs and the perceived effects on corporate resiliency - Soo, Seong Huat (2023)
Businesses are faced with an increasing turbulent environment. In order to survive in such an environment, businesses will need to learn. The Singapore government has launched Skillsfuture, a nation-wide learning initiative aim at up-skilling the individuals. However, little research has been conducted in understanding the effects. With COVID19 pandemic, it exemplifies the importance of knowing how can learning contribute to firms’ responses to crisis. Conducting literature review, it was found that literatures on Organizational Learning (including learning cultures) and corporate resiliency developed in parallel. Only a few research papers and books merge the two disciplines. To present a systematic analysis on the two topics, literatures are reviewed based on academics’ main thrust in their works into three categories, what constitutes Learning Culture, how is Learning Culture transmitted and why it makes sense for a company to develop learning culture. For corporate resiliency, literatures are reviewed primarily on two streams of studies, that of capacity-building to face disruptive events and those taking an opportunistic stance, favouring in-the-moment best reactions to disruptive events. The relationship between learning cultures and corporate resiliency are explained by mathematical equations and graphs which take into account of perceived effects and perceived values of what learning cultures have onto corporate resiliency. The conceptual framework was designed based on the research question and to guide subsequent sections into fulfilling its research objectives. Following, this research focus in freight forwarding industry, in particular, the Singaporean freight SMEs. 10 interviews were conducted with 10 respondents between early February 2023 to early March 2023 with the intention to find out COVID19 impacts, resilience topics and states of learning cultures in the industry. Collected data are analysed using NVIVO software. First, identifying drivers of learning cultures, second, grouping respondents answer in quadratic forms and finally run simulation on sentiments and relational themes to identify gaps and opportunities. The key finding is a near-perfect matching of industry cultural attributes to states of learning culture which correspond to four maturity levels in corporate resiliency. These inter-relational graphs of quadrants provide insights into leadership, performance, barriers of learning and allow for recommendations to be made to national learning initiatives policy. Academic framework and theory from earlier literature reviews find their relevance in comparing respondents’ traits within these quadrants. Subsequently, a name was provided for the inter-relational quadrants call QILCAR (Quadratic Inferences on Learning Cultures towards Resiliency).